Emotion Regulation Strategies on Family Functioning among Young Married Couples - Gita Irianda Rizkyani Medellu; Fathimah Adilla Azzahra (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2022)
This research aims to find the effect of emotion regulation with strategies like cognitive reappraisal and expressive suppression toward family functioning in young married couples in Indonesia. The General Functioning of The Family Assessment Device and Emotion Regulation Questionnaire were completed by married young adults aged between 18-25 years old. Multiple regression was used for data analysis. Results showed that emotion regulation significantly influences family functioning in married emerging adulthood. Furthermore, the partial measurement of cognitive reappraisal emotion regulation towards family functioning in a marital relationship in emerging adulthood showed a significant negative influence. Meanwhile, expressive suppression of emotion regulation predicts higher family functioning in married emerging adults. This study also showed that most respondents have healthy family functioning and use cognitive reappraisal in emotional regulation strategies for both genders. Furthermore, demographic data also showed the highest percentage using of expressive suppression among men than women. This research illustrates that individuals could achieve healthy family functioning during the age period of emerging adulthood. In addition, in the context of marital relationships among individuals in the emerging adulthood age period, there are also more adaptive emotion regulation strategies, the use of cognitive reappraisal emotional regulation strategies are better used by married emerging adults for better healthy family functioning in the family.